(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s ((3YHOGdQShd Hf YHOGdbGOQ GHf MSGe GdOjf GddGghQj GdLfGfj s)
(3ChdgG (B:s
(3CjgG GdbdH dG CQGc Jajb WGd eG bO JYdbJc GdYdhb ef jcf ef ghi MHjH bQjHG aEf GdfGRM GdHYjO GdSMjb s
(3BNQgG (B:s
(3hcGf YeGQI bO CNJd hGfbWY aj BNQ GdYeQ aUGQ Edi EHQGgje Hf SYOGf, hcGf bO Qhi Yfg TYQg GdbOje cdg hGddg JYGdi CYde gfG BNQ cJGH GdCZGfj GdcHjQ GdLGeY s
(3ajg SbW CKfGA PcQ GdgPdj hCNHGQgs
(3hjCJj HYOg PcQ YHjOGddg Hf bjS GdQbjGJ hfSHgs
(3hQO CjVkG JMJ Qbe (B2176s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs